Would Cajal or Ortega obtain researcher status nowadays? - Jiménez-Contreras, Evaristo; Ruiz-Pérez, Rafael; Delgado-López-Cózar, Emilio (Anuario ThinkEPI, 2009)
The validity of the Spanish system of scientific evaluation used in the selection and promotion of teaching and research faculty members and implemented through six-year terms (Cneai sexenios) or accreditation (Aneca), is discussed, due to the numerous criticisms that the system receives.
Keywords: Research evaluation systems; Research section; Spanish research evaluation system.